Role of Junctional Adhesion Molecule-C in the Regulation of Inner Endothelial Blood-Retinal Barrier Function - Hou, Xu; Du, Hong-Jun; Zhou, Jian; Hu, Dan; Wang, Yu-Sheng; Li, Xuri (Frontiers in Cell and Developmental Biology, 2021)
Although JAM-C is abundantly expressed in the retinae and upregulated in choroidal neovascularization, it remains thus far poorly understood whether it plays a role in the blood-retinal barrier, which is critical to maintain the normal functions of the eye. Here, we report that JAM-C is highly expressed in retinal capillary endothelial cells (RCECs), and VEGF or PDGF-C treatment induced JAM-C translocation from the cytoplasm to the cytomembrane. Moreover, JAM-C knockdown in RCECs inhibited the adhesion and transmigration of macrophages from wet age-related macular degeneration (wAMD) patients to and through RCECs, whereas JAM-C overexpression in RCECs increased the adhesion and transmigration of macrophages from both wAMD patients and healthy controls. Importantly, the JAM-C overexpression-induced transmigration of macrophages from wAMD patients was abolished by the administration of the protein kinase C (PKC) inhibitor GF109203X. Of note, we found that the serum levels of soluble JAM-C were more than twofold higher in wAMD patients than in healthy controls. Mechanistically, we show that JAM-C overexpression or knockdown in RCECs decreased or increased cytosolic Ca2+ concentrations, respectively. Our findings suggest that the dynamic translocation of JAM-C induced by vasoactive molecules might be one of the mechanisms underlying inner endothelial BRB malfunction, and inhibition of JAM-C or PKC in RCECs may help maintain the normal function of the inner BRB. In addition, increased serum soluble JAM-C levels might serve as a molecular marker for wAMD, and modulating JAM-C activity may have potential therapeutic value for the treatment of BRB malfunction-related ocular diseases.